Position of Policy Regulations (Beleidsregel) in the Indonesian Positive Law System - Novianti, Vera; Akbar, Muhamad Aksan; Rijal, Syamsul (Faculty of Law, Universitas Sembilanbelas November Kolaka, 2024)
The absence of regulations governing policy regulations has resulted in differences of opinion regarding the review of policy regulations, this is due to the unclear position of policy regulations in the Indonesian positive legal system. The aim of this research is to determine the position of policy regulations and the authority to review policy regulations in the Indonesian positive law system. This research uses normative legal research methods with a conceptual approach and a case approach using literature study and document study. The results obtained in this research are that policy regulations are not included in statutory regulations, the existence of policy regulations is based on free discretion carried out to complement deficiencies or weaknesses in the principle of legality which is always based on written statutory regulations. Testing of policy regulations can be done through executive review namely by submitting an objection to the official who issued the policy regulation and appealing to the superior of the official who issued the policy regulation as an initial effort and judicial review to the Supreme Court with basic principles the court knows and jurisprudence if efforts executive review did not succeed.